2020
DOI: 10.1002/pros.24039
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of stemness‐associated markers in the development of castration‐resistant prostate cancer

Abstract: BackgroundPutative castration‐resistant (CR) stem‐like cells (CRSC) have been identified based on their ability to initiate and drive prostate cancer (PCa) recurrence following castration in vivo. Yet the relevance of these CRSC in the course of the human disease and particularly for the transition from hormone‐naive (HN) to castration‐resistance is unclear. In this study, we aimed at deciphering the significance of CRSC markers in PCa progression.MethodsWe constructed a tissue microarray comprising 112 matche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 42 publications
1
24
0
Order By: Relevance
“…Consistently with those findings, Magnen and co-authors found an association of ALDH1A1 with higher-grade tumors (Magnen et al, 2013). A recent study by Federer-Gsponer also indicated patterns of mutual exclusivity for ALDH1A1 and ALDH1A3 expression across several datasets (Federer-Gsponer et al, 2020). However, the relationship between ALDH genes and bone metastatic tumor growth was unknown.…”
Section: Discussionmentioning
confidence: 87%
“…Consistently with those findings, Magnen and co-authors found an association of ALDH1A1 with higher-grade tumors (Magnen et al, 2013). A recent study by Federer-Gsponer also indicated patterns of mutual exclusivity for ALDH1A1 and ALDH1A3 expression across several datasets (Federer-Gsponer et al, 2020). However, the relationship between ALDH genes and bone metastatic tumor growth was unknown.…”
Section: Discussionmentioning
confidence: 87%
“…Besides Nkx3.1-expressing CARNs, other forms of cancer stem cell (CSC) have been identified that give rise to castration-resistant prostate cancers (CRPC). One such example includes cancer-associated fibroblasts (CAF) (83)(84)(85).…”
Section: Nkx31 and Stemnessmentioning
confidence: 99%
“…Because EZH2 was not assessed in this dataset, we ascertained its upregulation with disease progression on a tissue microarray of 33 primary and matched CRPC samples ( Supplementary Fig. 1G) 36 .…”
Section: Trajectory Analysis Quanti Es the Path To Disease Progressionmentioning
confidence: 99%
“…Immunohistochemically staining EZH2 protein expression was analyzed on a previously described tissue microarray including, matched primary and CRPC samples 36 . All prostate cancer samples were obtained under approval by the Ethics Committee of Northwestern and Central Switzerland (EKNZ, No EK/1311 and 2015/228).…”
Section: Plasmidsmentioning
confidence: 99%
See 1 more Smart Citation